2011
DOI: 10.1177/1071181311551190
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Task-Set Switching Ability, Not Working Memory Capacity, Predicts Change Blindness Sensitivity

Abstract: Individual differences in working memory capacity (WMC) have been shown to predict how well people perform tasks that require directed attention, but the individual differences responsible for task-set switching and noticing behaviors are less well understood. In this study, 86 undergraduate students from California State University, Northridge completed a measure of WMC, a measure of cognitive flexibility, and attempted to identify disappearing objects in change-blindness slides. WMC was not related to our me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This ability is indispensable in stress management of teachers who are often faced with student- or parent-related issues that are difficult to resolve. It has also been pointed out that cognitive flexibility contributes to not only prevention of burnout but also nurturing of prompt judgment for difficult tasks and improvement of the ability to recognize even a slight environmental change and to cope with it [ 18 , 29 ]. Teachers are also required to have the ability to promptly cope with consecutive daily problems and to quickly notice and react to changes in the atmosphere of students and the class.…”
Section: Discussionmentioning
confidence: 99%
“…This ability is indispensable in stress management of teachers who are often faced with student- or parent-related issues that are difficult to resolve. It has also been pointed out that cognitive flexibility contributes to not only prevention of burnout but also nurturing of prompt judgment for difficult tasks and improvement of the ability to recognize even a slight environmental change and to cope with it [ 18 , 29 ]. Teachers are also required to have the ability to promptly cope with consecutive daily problems and to quickly notice and react to changes in the atmosphere of students and the class.…”
Section: Discussionmentioning
confidence: 99%
“…Resources must be allocated continuously for successful completion on the task. Some researchers have found that the vigilance decrement can be experienced as soon as 10 minutes (Figueroa and Youmans, 2011).…”
Section: Sustained Attentionmentioning
confidence: 99%
“…This performance decrement, therefore, seems to reflect something more related to attentional abilities than to deliberate strategies. Future research should investigate factors contributing to this deficiency by low-PAC individuals (e.g., working memory capacity and cognitive flexibility; Bühner, König, Pick, & Krumm, 2006;Feldman Barrett et al, 2004;Youmans, Figueroa, & Kramarova, 2011) and possible training or interfaces design strategies to mitigate them.…”
Section: Discussionmentioning
confidence: 99%